NOTARY LIABILITY FOR THE DEED OF LOAN AND LOAN AGREEMENT THAT IS LEGALLY DEFECTIVE AND CANCELED BY THE JUDGE : STUDY OF DECISION NUMBER 22/PDT/2017/PT. AMB - Priyanto, Gagah Putra; Suraji, Suraji; Nugraheni, Anjar Sri Ciptorukmi (ANAYASA : Journal of Legal Studies, 2025)
Deeds made by a notary, such as a deed of agreement, sale and purchase deed, or grant deed, have the force of law that binds the parties involved. Notaries are obliged to carry out their profession with full dedication and integrity. The purpose of this study is to find out the responsibility of the Notary for the legally defective Deed of Borrowing Agreement and to find out the legal consequences for the Deed of Borrowing Agreement that is legally defective and canceled by the judge. This legal research is a type of Normative legal research. The result of this study is that the cancellation of the agreement has a retroactive effect that cancels all rights and obligations previously regulated in the agreement. The status of the deed as an authentic document is lost, so its evidentiary power declines and can only be considered as a deed under hand.